The course of spinal tuberculosis (Pott disease): results of the multinational, multicentre Backbone-2 study. (November 2015) - Batirel, A.; Erdem, H.; Sengoz, G.; Pehlivanoglu, F.; Ramosaco, E.; Gülsün, S.; Tekin, R.; Mete, B.; Balkan, İ.İ.; Sevgi, D.Y.; Giannitsioti, E.; Fragou, A.; et al.
Abstract: We aimed to describe clinical, laboratory, diagnostic and therapeutic features of spinal tuberculosis (ST), also known as Pott disease. A total of 314 patients with ST from 35 centres in Turkey, Egypt, Albania and Greece were included. Median duration from initial symptoms to the time of diagnosis was 78 days. The most common complications presented before diagnosis were abscesses (69%), neurologic deficits (40%), spinal instability (21%) and spinal deformity (16%). Lumbar (56%), thoracic (49%) and thoracolumbar (13%) vertebrae were the most commonly involved sites of infection. Although 51% of the patients had multiple levels of vertebral involvement, 8% had noncontiguous involvement of multiple vertebral bodies. The causative agent was identified in 41% of cases. Histopathologic examination was performed in 200 patients (64%), and 74% were consistent with tuberculosis. Medical treatment alone was implemented in 103 patients (33%), while 211 patients (67%) underwent diagnostic and/or therapeutic surgical intervention. Ten percent of the patients required more than one surgical intervention. Mortality occurred in 7 patients (2%), and 77 (25%) developed sequelae. The distribution of the posttreatment sequelae were as follows: 11% kyphosis, 6% Gibbus deformity, 5% scoliosis, 5% paraparesis, 5% paraplegia and 4% loss of sensation. Older age, presence of neurologic deficit and spinal deformity were predictors of unfavourable outcome. ST results in significant morbidity as a result of its insidious course and delayed diagnosis because of diagnostic and therapeutic challenges. ST should be considered in the differential diagnosis of patients with vertebral osteomyelitis, especially in tuberculosis-endemic regions. Early establishment of definitive aetiologic diagnosis and appropriate treatment are of paramount importance to prevent development of sequelae.